Mihhail Kurotškini panus udmurdi folkloristikasse - Alevtina Kamitova (Mäetagused)
The work presents little-known and new facts from the life and work of the educator and teacher Mikhail Alekseevich Kurochkin. He made a valuable contribution to the preservation and popularization of the folklore heritage of the Udmurt people and the development of musical culture. Hardly accessible and interesting factual stories about his creative and life biography have been introduced into scientific circulation; these were identified during work with newspaper materials, documents from the archives of the Administration of Sarapul and the archives of the Mozhginsky Pedagogical College by Trofim Kuzmich Borisov. Some features of the song collection Kubyz (1925) with notes by Mikhail Kurochkin are described. The book was compiled by him on the basis of folkloric field materials collected together with students of the Mozhginsky Technical School. His pedagogical and cultural activities contributed to the development of children’s interest in their native culture, the formation of a musical direction in Udmurt science, and the education of new national personnel. The study of the life and creative biography, educational and folklore activities of Mikhail Kurochkin made it possible to determine his significant contribution to the cultural life of the Udmurt people at the beginning of the 20th century.